Resisting AI : an anti-fascist approach to artificial intelligence - McQuillan, Dan (Daniel Mark Thomas) (Bristol University Press, 2022)
Artificial Intelligence (AI) is everywhere, yet it causes damage to society in ways that can't be fixed. Calling for the restructuring of AI, Dan McQuillan sets out an anti-fascist approach that replaces exclusions with caring and outlines new mechanisms that support collective freedom.